30. EVALUATION OF CHANGES IN EFFECTIVE COMMUNICATION CRITERIA BASED ON THE AIDET MODEL AMONG NURSING STUDENTS OF THANG LONG UNIVERSITY AT CLINICAL SITES IN THE ACADEMIC YEAR 2024-2025 (Vietnam Journal of Community Medicine, 2025)
Objective: To assess the changes in effective communication criteria among nursing students of Thang Long University before and after a training intervention based on the AIDET model.Subjects and methods: A one-group pretest-posttest quasi-experimental study was conducted on second and third-year nursing students who had completed the physical assessment course and were undertaking clinical practice at hospitals from August 2024 to June 2025. Students were observed by the researchers during communication with patients and assessed using a structured checklist consisting of five AIDET - based criteria: Acknowledge, Introduce, Duration, Explanation, and Thank you. Assessments were performed at two time points: immediately before and after the intervention.Results: The mean AIDET practice score increased significantly from 4.62 ± 3.26 to 8.61 ± 1.09, with a statistically significant difference (p < 0.001).Conclusion: The application of the AIDET model significantly improved the communication skills of nursing students in real patient interactions. The proportion of students performing well and the mean scores for AIDET criteria increased markedly after the intervention.
Keywords: Communication practice, AIDET model, nursing students.